(untitled) (REVISTA SAYWA, 2024)
A scientific account of the expedition to the wreck of the Titanic, which departed from St John’s, Newfoundland, on 16 June aboard the research and expedition vessel MV Polar Prince. During the mission, the submersible in which five people were travelling tragically imploded.